The Philosophical Value and Urgency of Deep Learning in Islamic Education: A Study on Teachers’ Perspectives - Fathurohim; Frendi Fernando; Aniroh; Galih Prayoga; Muhamad Habib; Supriyanto; Vivit Andianingsih (Institut Agama Islam An-Nawawi Purworejo, 2025)
The urgency of applying deep learning approaches in Islamic Religious Education (IRE) is increasingly relevant in the digital age, which demands meaningful and character-building learning, not just memorization. This study aims to analyze the opportunities and challenges of implementing deep learning approaches in the context of IRE in Indonesia. Using qualitative methods with a case study approach and thematic analysis of the perspectives of IRE teachers, this study explores the perceptions, practices, and obstacles encountered in the implementation process. The results show that teachers generally welcome this approach positively because it is considered capable of enhancing creativity and the relevance of IRE values to real life. However, its implementation is still hampered by limited resources, low conceptual understanding, resistance to paradigm shifts, and a lack of ongoing training. Further analysis reveals the alignment between the principles of meaningful, mindful, and joyful learning with Islamic values such as tafakkur, akhlak, and ibadah in the learning process. In conclusion, the application of deep learning in PAI requires synergy between teachers, educational institutions, and policymakers to optimize the integration of spiritual values with modern pedagogical methods. This study recommends strengthening teacher capacity and adaptive curriculum policies as strategic steps towards a more holistic and contextual transformation of PAI learning.